The Influence of ZIS, Islamic Human Development Index, and Investment on Indonesia's Economic Growth: An ECM Model Analysis - Faizi; Latifah, Nahsa Noor (Ijtimā iyya Journal of Muslim Society Research, 2024)
Economic growth refers to the generation of additional income for a society within a specific time frame through economic activities. This is often measured by GDP. However, despite an increase in GDP, Indonesia's economic growth as a developing country is still considered unoptimal. Therefore, the purpose of this research is to analyze the impact of ZIS, I-HDI, FDI, and Domestic Investment on Indonesia's economic growth from 2013 to 2022, spanning ten years. This study adopts a quantitative approach and uses an ECM model. The findings indicate that ZIS, I-HDI, and Domestic Investment have a significant positive long-term effect on economic growth, but their impact is not significant in the short term. Conversely, FDI has an insignificant negative effect on both long-term and short-term economic growth. When analyzing all the factors simultaneously, the results demonstrate that ZIS, I-HDI, FDI, and Domestic Investment collectively have a significant effect on economic growth in both the long and short term. Building on these findings, policymakers should delve deeper into the specific mechanisms through which ZIS, the Islamic Human Development Index, FDI, and Domestic Investment influence economic growth in both the short and long term. By understanding the intricate connections between these factors and economic growth, policymakers can develop more targeted and effective strategies to promote sustainable and balanced economic development.